ANALYSIS OF PLANT-BASED FOOD PRODUCTS IN THE DIETARY RATIONS OF STUDENT-ATHLETES (Global Conference on Medical and Health Sciences, 2026)
Adequate nutrition, ensuring the replenishment of energy expenditures and meeting the needs of a young athlete’s body for plastic materials and biologically active substances, is an essential condition for the normal course of growth and development processes, maintaining high physical and mental performance, accelerating adaptation to environmental factors and physical loads, reducing post-exercise recovery time, and preventing diseases associated with nutritional factors [1, 2].